Electronic data processing - Emery, Glyn. (London : Pitman, 1975)
It is the aim of this book to point out some of the main principles underlying the design of computer systems, and to show how different solutions to the same problems can give rise to different features in assembly languages and operating systems.
Includes bibliographical references.
ijb 16/01/2019
Loans
Keywords: Electronic data processing; Electronic digital computers